RISK OF HYPERTENSION WITH MULTICYSTIC KIDNEY DISEASE : A SYSTEMATIC REVIEW - Ramadhani, Rizkia Amal (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Background: Multicystic dysplastic kidney (MCDK) is a congenital cystic kidney disease that can be incidentally seen during the antenatal ultrasound. The condition is most commonly asymptomatic. The clinical presentation is usually characterized by multiple small cysts or a single dominating cyst in the fetal kidney depending on the type of MCDK. Most cases undergo spontaneous involution, and complications like hypertension, infection, and malignancy are rare. Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2013 and 2023 were taken into account. Several different online reference sources, like Pubmed and SagePub, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: In the PubMed database, the results of our search brought up 563 articles, whereas the results of our search on SagePub brought up 5 articles. The results of the search conducted for the last year of 2013 yielded a total 6 articles for PubMed and 3 articles for SagePub. In the end, we compiled a total of 5 papers, 2 of which came from PubMed and 1 of which came from SagePub. We included five research that met the criteria. Conclusion: Although the risk of hypertension in MCKD is low, the results of this study do not allow firm recommendations on the frequency and duration of blood pressure measurement follow up for these children. Large prospective cohort studies with a very long duration of follow up are needed.